Interaction of Magnesia with Limestone-Metakaolin-Calcium Hydroxide Ternary Alkali-Activated Systems - A. Cwirzen; L. Metsäpelto; K. Habermehl-Cwirzen (Advances in Materials Science and Engineering)
The effect of magnesia on ternary systems composed of limestone, metakaolin and calcium hydroxide, alkali activated with sodium silicate, sodium hydroxide, and sodium sulphate was studied by determination of the compressive strength, X-ray powder diffraction (XRD), thermogravimetry (TG), and scanning electron microscope (SEM). Pastes activated with sodium silicate and sodium sulphate showed strength regression caused by a formation of an unstable prone to cracking geopolymer gel. The presence of magnesia in sodium hydroxide-activated system hindered this trend by promoting a formation of more stable crystalline phases intermixed with brucide. In general, magnesia densified the binder matrix by promoting a formation of amorphous phases while sodium hydroxide produced the most porous microstructure containing high amount of crystalline phases.